KAJIAN PATOGENISITAS Beauveria bassiana dan Metarhizium sp TERHADAP LARVA ULAT GRAYAK (Spodoptera frugiperda) PADA TANAMAN JAGUNG - Yasir Harun; Ayu Kartini Parawansa; Abdul Haris (Percetakan Umi Toaha Makassar, 2022)
Spodoptera frugiperda is an important pest on maize. The purpose of this research were to determine the pathogenicity of Beauveria bassiana and Metharizium sp in Fall armyworm (S. frugiperda) larvae, to determine the effective concentrations of B. bassiana and Metarhizium sp. to control Fall armyworm (S. frugiperda), and to determine the time span of B. bassiana and Metarhizium sp infection which is effective for controlling Fall armyworm (S. frugiperda). This research was conducted at the Pesticide and Natural Materials Laboratory, Faculty of Agriculture, Universitas Muslim Indonesia, Makassar, UPTD Balai Proteksi of South Sulawesi and Corn Planting in Galung Village, Barru District. Barru Regency. The research start on April to October 2020. The research used a Fully Randomized Design (FRD) with 2 factors and three repetition. The first factor was the type of fungus (Metarhizium sp and B. bassiana) and the second factor was the density of conidia (10⁶, 10⁷, 10⁸ and 10⁹ conidia/ml). The results showed that the type of fungus and the density of conidia were significantly different for all observed variables. The pathogenicity of the fungus B. bassiana was better than Metarhizium sp and the density of conidia (concentrations) of both B. bassiana and Metarhizium sp. were significantly different from those of S. frugiperda larvae, but the density of conidia (concentration) 10⁹ was faster infected and killed S. frugiperda larvae. The Symptoms of entomopathogenic fungus attack on S. frugiperda larvae are sluggish movement, turning pale in color, decreased appetite, gradually silence, and death. The dead larvae are hardened and slightly blackened.